m+8m+9m-9=

Simple and best practice solution for m+8m+9m-9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+8m+9m-9= equation:


Simplifying
m + 8m + 9m + -9 = 0

Reorder the terms:
-9 + m + 8m + 9m = 0

Combine like terms: m + 8m = 9m
-9 + 9m + 9m = 0

Combine like terms: 9m + 9m = 18m
-9 + 18m = 0

Solving
-9 + 18m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 18m = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 18m = 0 + 9
18m = 0 + 9

Combine like terms: 0 + 9 = 9
18m = 9

Divide each side by '18'.
m = 0.5

Simplifying
m = 0.5

See similar equations:

| 3(x-2)=5(x+1)-1 | | 8+3e=29 | | 24r+18ry-4xr-3xy= | | 8r+s-7s=0 | | m=-1/4 | | 8x+6=8x-3 | | 19-13p=-16p-5 | | 1/12w-3/2=-3/4w+11/6+1/2w | | 9y=4x+12 | | h=16+32t+-16t^2 | | 3x+10-6x=20 | | 2x-1=9.5 | | (-5ab+6a-1)-(-5ab-8)= | | 4x-2(x-5)=-6+5x-2 | | -2x-10=-4x+12 | | (6x-9)/3=x | | 2*2/3=x | | 3x+1=9.5 | | -0.5-0.8= | | x^(1/3)-25x^(1/2)=0 | | 9x+5x=7forx | | 3x+4=-x+16 | | 15(-42x+40)=15(-8x+244)e | | (1/2+i)-(2/1+2i) | | 5c-5+10=24 | | -3(p+9)-3(2p-1)-17p= | | 18y-20y=0 | | 15(-42x+40)=15(8x+244) | | (2/3)x=2,25 | | 7(x-3)+x=2(2x-5)-19 | | 20(2-50)=19000 | | 2+4/3=X |

Equations solver categories